Ideology - McLellan, David (Rawat, 2019)
To study ideology is to ask such questions as: Where do our ideas about society and politics come from? Are such ideas socially determined? If so, what validity can they claim? In this brief yet comprehensive introduction, David McLellan looks at the origins of the concept of ideology, analyzes its use in the Marxist and non-Marxist traditions, and assesses the various uses to which it has been put in recent social and political theory, particularly the connection between ideology and the “end of history” debate.